2005
DOI: 10.1007/s00213-005-0177-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a subanesthetic dose of ketamine on verbal memory in normal volunteers

Abstract: This study characterizes the behavioral effects associated with ketamine and suggests that ketamine decreases verbal memory performance by interfering with early consolidation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 30 publications
4
56
0
Order By: Relevance
“…In laboratory experiments, a subanesthetic dose of ketamine given to normal volunteers induces the symptoms of schizophrenia more effectively than any other known drug [29][30][31][32]. NMDA antagonists reproduce both negative and positive symptoms, as well as many of the cognitive deficits associated with the disease.…”
Section: Nmda Hypofunctionmentioning
confidence: 99%
“…In laboratory experiments, a subanesthetic dose of ketamine given to normal volunteers induces the symptoms of schizophrenia more effectively than any other known drug [29][30][31][32]. NMDA antagonists reproduce both negative and positive symptoms, as well as many of the cognitive deficits associated with the disease.…”
Section: Nmda Hypofunctionmentioning
confidence: 99%
“…At low doses, ketamine interfered primarily with early consolidation of memory, reducing the delayed recall of words presented immediately before but not during infusion of the drug. 60 Different doses of anesthetics have different effects on the time-dependent types of memory. Generally, low doses of anesthetics leave very short-term memory intact, such that patients can carry on a conversation and appear to be lucid.…”
Section: Blockade Of Memory By General Anesthetics In Humans and Labomentioning
confidence: 99%
“…In healthy volunteers, ketamine reliably results in acute impairments in learning and memory (Krystal et al, 1994;Krystal et al, 1999;Krystal et al, 2005;Morgan et al, 2004;Parwani et al, 2005;Perry et al, 2007). Most studies of neurocognition in healthy volunteers have utilized a dosing strategy distinct from what has been utilized in clinical trials for depression to date.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Krystal et al (2005) used a 1-min IV infusion of 0.23 mg/kg of ketamine followed by a 1-h infusion of 0.5 mg/kg in a neurocognitive study in healthy volunteers and assessments were conducted during the drug infusion. Some studies have found evidence for selective impairments in aspects of executive functioning related to ketamine (Krystal et al, 1994;Krystal et al, 1999), whereas other studies have found no impairments (Morgan et al, 2004;Parwani et al, 2005).…”
Section: Introductionmentioning
confidence: 99%